Participle as Seen in The Jakarta Post Headings - Dwiana Marcheni Arumningtyas (Lexicon, 2012)
This paper discusses the usage of participle as seen in The Jakarta Post Headings. The Jakarta Post is considered as a representative newspaper especially for Non Native English Language Learners for it is mostly written by Indonesian journalists using good standard of English. The data of this research are taken from The Jakarta Post edition September 6 until October 6, 2012. The headings are classified based on the type of participle they contained. Afterwards, they are analyzed based on their context in order to figure out the meaning they might contain. Lastly, this paper talks about the prevalence of the participle in The Jakarta Post headings which may reflect the preference of participles used by Indonesian authors in expressing their idea in English. As the result, this paper points out the 5 patterns of present participle, and 6 patterns of past participle used in The Jakarta Post, their meaning, and their frequency.